(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
This investigation is based on the directress of direction towards the base in the taking of decisions to fortify the logistics that your integration appears as the economic activity of an organization that nourishes of the processes of supplying to secure the productive process. This enterprise has influence directly never social of the territory and contributes your grain of sand in the export. It is for this reason that is worked with objective strategists to achieve a better positioning with respect to all the other factors that participate with this objet social. Non-lacking, in this work a methodology that it is the indispensable purpose to demonstrate strategic environment of the entity and for if are little the forms in which it is presented the procedures and proposals of improvement by giving the measure of the scientific sight that the investigation proposes.